New Small Compounds Based on Thienylenevinylene with D-A-D Structure for BHJ Applications: Theoretical Study - Aziz El Alamy; Mohamed Bourass; Amina Amine; Rachid Kcimi; Mohammed Bouachrine (Orbital: The Electronic Journal of Chemistry, 2020)
In this work, ten new small molecules based on Thienylenevinylene as a donor and heterocyclic group A as acceptor of electrons with the donor-acceptor-donor D-A-D structure were studied by density functional theory (DFT) and time-dependent DFT (TDDFT) methods using the Gaussian09 program. The geometric and electronic properties of these compounds have been analyzed and reported by using the DFT /B3LYP level with 6-31G (d,p) basis set. Thus, we calculated the optical properties (absorption/emission) using the TDDFT/CAM-B3LYP/6-31G (d,p) method. The influence of the change of acceptor (π-linker) on the electrochemical, photovoltaic and optic properties has been investigated and discussed. The studied compounds have low energy gap which decreases by going from C1 to C10, this improve the intramolecular charge transfer in these molecules. This work shows that the studied compounds are promising and have good properties for optoelectronic and photovoltaic applications, especially in BHJ solar cells with maximum power conversion efficiency (PCE) of 10% for C7 and C9.DOI: http://dx.doi.org/10.17807/orbital.v12i4.1524